A new integral transform and associated distributions - Eltayeb, Hassan; Kilicman, Adem; Fisher, Brian (Taylor & Francis, 2010)
In this paper, we generalize the concepts of a new integral transform, namely the Sumudu transform, to distributions and study some of their properties. Further, we also apply this transform to solve one-dimensional wave equation having a singularity at the initial conditions.